Pemanfaatan Media Pembelajaran Berbasis Teknologi sebagai Alat Pembelajaran Kekinian bagi Guru Profesional IPS dalam Penerapan Pendidikan Karakter Menyongsong Era Society 5.0 - Eni Rahayu Widyawati; Sukadari Sukadari (UM Purwokerto Press, 2023)
The writing of this article aims to (1) find out the optimal use of technology-based learning media as a contemporary learning tool for social studies professional teachers; (2) explore the utilization of technology-based learning media as a contemporary learning tool in implementing students' character education; (3) identify the roles and challenges of social studies professional teachers in utilizing technology-based learning media as a contemporary learning tool in students' character education towards the Era of Society 5.0. The method used in writing this article is descriptive qualitative, employing a literature review approach to collect relevant data from various academic sources such as books, journals, magazines, brochures, websites, and other references related to the topic of